IN VITRO ANTIOXIDANT ACTIVITY OF CTIVITY OF CTIVITY OF LAUNAEA PINNATIFIDA CASS LEAVES - NAGALAPUR, SANTOSH KUMAR; S. PARAMJYOTHI (The Bioscan, 2010)
The antioxidant activities of petroleum ether, chloroform, ethanol and water extracts of the leaves of Launeae pinnatifida Cass were determined by ferric reducing power, free radical scavenging activity by 1, 1-Diphenyl2-picrylhydrazyl (DPPH) and hydroxyl radical scavenging activity. The total amount of phenols and flavonoids were estimated to be 179.46 ± 0.71 mg/g as gallic acid equivalents and 87.46 ± 0.37 mg/g as quercetin equivalents respectively in ethanolic extract. The ethanolic extract exhibited the significant activity against DPPH free radical compared to the other extracts. Ethanol and water extracts gave similar and significant high levels of hydroxyl radical scavenging activities when compared with the standard. Chloroform and petroleum ether extracts showed almost similar results. The results obtained in the present study thus indicate that the ethanolic extract is the potential source of antioxidant.